2023
DOI: 10.3390/brainsci13020289
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Rosmarinic Acid In Vitro and In Vivo Models of Epileptiform Activity Induced by Pilocarpine

Abstract: Epilepsy is characterized by a predisposition to generate recurrent and spontaneous seizures; it affects millions of people worldwide. Status epilepticus (SE) is a severe type of seizure. In this context, screening potential treatments is very important. In the present study, we evaluated the beneficial effects of rosmarinic acid (RA) in pilocarpine-induced in vitro and in vivo models of epileptiform activity. Using an in vitro model in combined entorhinal cortex–hippocampal from Wistar rats we evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In response to lipopolysaccharide, SOD 3 was released from intracellular stores of macrophages producing biological responses [49]. Lactate has been considered a useful seizure-like activity biomarker, as demonstrated by an increase in its levels in the extracellular environment of the human hippocampus during seizures; rosmarinic acid (30 mg/kg/body volume) was able to reduce pilocarpine-stimulated lactate release in the brains of epileptic male rats [50]. Gap junctions that allow direct transfer of ions and molecules between neighboring cells, and gap junctions between astrocytes, play an important role in the development of brain diseases such as epilepsy [51].…”
Section: Discussionmentioning
confidence: 99%
“…In response to lipopolysaccharide, SOD 3 was released from intracellular stores of macrophages producing biological responses [49]. Lactate has been considered a useful seizure-like activity biomarker, as demonstrated by an increase in its levels in the extracellular environment of the human hippocampus during seizures; rosmarinic acid (30 mg/kg/body volume) was able to reduce pilocarpine-stimulated lactate release in the brains of epileptic male rats [50]. Gap junctions that allow direct transfer of ions and molecules between neighboring cells, and gap junctions between astrocytes, play an important role in the development of brain diseases such as epilepsy [51].…”
Section: Discussionmentioning
confidence: 99%
“…A study investigated the potential advantages of RA in both in vitro and in vivo models of epileptiform activity induced by pilocarpine. This study revealed RA's potential to reduce the acute neuromotor disturbances and oxidative damage triggered by status epilepticus (SE) in mice [68]. Furthermore, it appears to offer favourable effects in in vitro models of epileptiform activity, as evidenced by a decrease in lactate release.…”
Section: Epilepsymentioning
confidence: 93%
“…RA doses of 100 µg/mL significantly inhibited the activity of gammaaminobutyric acid transaminase (GABA-T) [67]. Numerous reports showed the protective role of RA in animal models and in vitro studies against epilepsy [68,69]. A study investigated the potential advantages of RA in both in vitro and in vivo models of epileptiform activity induced by pilocarpine.…”
Section: Epilepsymentioning
confidence: 99%